Energy Efficiency of the Extrusion Process and its Effect on Output of Biogas during the Fermentation of Maize and Rape Straw - Zablodskiy M.; Klendiy P.; Dudar O.; Babak D. (Problems of the Regional Energetics)
The purpose of the research is determining the influence of pre-treatment by extrusion of rape and maize straw on the output of biogas and the energy efficient mode of the extrusion process. The set goal is achieved by solving the following problems: pre-treatment of rape and maize straw by grinding and various versions of extrusion; carrying out experimental researches of the fermentation of rape and maize straw in the mesophilic mode of fermentation for 42 days; carrying out numerical modeling to determine the power inputs on the process of extrusion during change the frequency rotation of screw conveyer of the extruder. The most significant results: it was experimentally proven that the output of biogas from rape and maize straw increases when the size of their particles is reduced to a certain value, which is reached after 2-times extrusion, and further reduction of the size of the particles does not give a positive effect and, vice versa, reduces gas release. Extrusion provides not only grinding, but also thermo-baro processing, which additionally grinds lignin-cellulosic raw material. It was determined that the energy efficient mode of operation, the necessary level of pressure and temperature in the die, which exclude the burning of organic raw materials, is ensured at the rotation frequency of screw conveyer of the extruder at 110 r/pm. The significance of the obtained results is that the extrusion with the proposed technological and mode parameters of the extruder can be used as an effective method of pre-treatment of lignin-cellulosic raw material to increase the productivity of bioreactors and biogas output.